Analysis of Profitability and Leverage on Company Value with Size and Growth Capacity as Moderating Variables in the Property Sector - Qurrotu’ainii, Hasnaa Rizky Putri; Hermuningsih, Sri; Suyanto, Suyanto (Almana : Jurnal Manajemen dan Bisnis, 2025)
This study analyzes the effect of profitability (ROA) and leverage (DER) on firm value (Tobin's Q), with firm size and growth capacity as moderating variables in property companies listed on the Indonesia Stock Exchange (IDX) for the 2020–2024 period. The research method uses a quantitative approach with WarpPLS analysis techniques. The results show that ROA has a positive but insignificant effect on firm value, while DER has a positive and significant effect. Firm size and growth capacity are unable to moderate the relationship between profitability and leverage on firm value. These findings confirm that financing decisions through leverage are a dominant factor in increasing firm value, and support Signaling Theory and Pecking Order Theory regarding the importance of capital structure and financial information for investors.